PENGEMBANGAN SOAL HOTS BERBASIS TEORI BRUNER BERBANTUAN ANIMASI POWERPOINT PADA MATERI OPERASI BILANGAN PECAHAN - Adhi Nugroho, Sulistyono; Rusnilawati (Program Studi PGMI, 2025)
Research problems include the lack of HOTS questions, the absence of animation-based mathematics questions, and the lack of enthusiasm among students to study mathematics. The purpose of the study is to characterize the efficacy, viability, and validity of the developed HOTS questions. The benefits of this research include providing references for teachers in developing HOTS questions, helping students improve their cognitive abilities, and improving the quality of mathematics education in schools. This research focuses on developing higher order mathematical thinking (HOTS) questions which are presented in the form of PowerPoint animations. The development process follows the Tessmer model, which includes initial preparation, appraisal of oneself, review by an expert, individual testing, testing in small groups, and field testing. The product developed is a collection of HOTS mathematics questions for elementary school students, intended to improve their maths learning results and motivation. This research also analyzes HOTS questions in textbooks and workbooks, designs HOTS questions based on Bruner's theory, and validates the questions with experts and students. The data collected includes quantitative data from validation and field testing, as well as qualitative data from feedback and suggestions from experts. Data were analyzed using various techniques, including validity analysis and coefficient calculations.